A Political Linguistic Investigation of Illocutionary Forces In Theresa May’s Speech on Brexit - Mey Linda, Triana; Susanto, Fajar (JET ADI BUANA, 2022)
The purpose of this research is to investigate the illocutionary force uttered by Theresa May which focuses on political aspects in the context of Brexit and how the illocutionary force is responded by people.  In conducting this research, qualitative research was used to describe two kinds of data: utterances containing illocutionary force in Theresa May’s speech on Brexit and responses to those illocutionary forces. The results of the research based on Theresa May’s speech on political aspects of Brexit are emphasized on the international relationship, law and regulation, geographical border, and government. The responses based on the illocutionary forces uttered by Theresa May in her speech on Brexit were to persuade British people that Brexit was right to do. Aside from that, it was used to relieve British’s fear towards Brexit. Those illocutionary forces were well inferred by the responders because the writer found the relevance between the illocutionary forces and its responses.